Anaesthetic management of a case of Treacher - Collins syndrome - Chowdhury, Md Shahnewaz; Chowdhury, Md Mohsinuzzaman; Chowdhury, Gulshan Ara (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Treacher-Collins syndrome (TCS) is a rare congenital disease known to be associated with a difficult airway and represents some of the most hazardous and difficult challenges that anaesthetists may encounter during their entire practice of anesthesia. Successful anaesthetic management of a case with Treacher-Collins syndrome posted for laparoscopic cholecystectomy under general anaesthesia is presented in this report. DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18178 Journal of BSA, 2009; 23(2): 72-75